Towards Student-Ready Mathematics Departments: Creating a Mathematics Placement Experience Within an Asset Framed Approach. Issue 10 (26th November 2021) - DiGregorio, G.; Hagman, J. Ellis
Abstract : As higher education institutions focus on increasing mathematics success, it is important to consider the experiences and needs of structurally disadvantaged identities. In this article, an asset-based framework was used to examine how eight first-generation, low-income, Students of Color perceive their mathematics placement experience. Although mathematics departments intend placement to be a mechanism for promoting success in mathematics, our research showed that the mathematics placement exam caused anxiety among students, was perceived as high stakes, and was viewed with a fixed mindset as opposed to a growth mindset. Implications of these insights encourage mathematics departments to consider alternative placement approaches that enhance the student experience of placement, especially for students with structurally disadvantaged identities. Creating an asset framed mathematics placement process is an initial step to improve success in mathematics.